Long‐Term Pooled Safety Analysis of Palbociclib in Combination with Endocrine Therapy for Hormone Receptor‐Positive/Human Epidermal Growth Factor Receptor 2‐Negative Advanced Breast Cancer: Updated Analysis with up to 5 Years of Follow‐Up. (10th March 2021) - Finn, Richard S.; Rugo, Hope S.; Gelmon, Karen A.; Cristofanilli, Massimo; Colleoni, Marco; Loi, Sherene; Schnell, Patrick; Lu, Dongrui R.; Theall, Kathy Puyana; Mori, Ave; Gauthier, Eric; Bananis, Eustratios; et al.
Abstract: Background: Previous studies demonstrated the tolerability of palbociclib plus endocrine therapy (ET). This analysis evaluated safety based on more recent cutoff dates and a longer palbociclib treatment exposure. Patients and Methods: Data were pooled from three randomized studies of patients with hormone receptor‐positive/human epidermal growth factor receptor 2‐negative (HR+/HER2−) advanced breast cancer (ABC), including postmenopausal women who had not received prior systemic treatment for advanced disease (PALOMA‐1/‐2) and pre‐ and postmenopausal women who had progressed on prior ET (PALOMA‐3). Results: Updated cutoff dates were December 21, 2017 (PALOMA‐1), May 31, 2017 (PALOMA‐2), and April 13, 2018 (PALOMA‐3). Total person‐years of treatment exposure were 1, 421.6 with palbociclib plus ET ( n = 872) and 528.4 with ET ( n = 471). Any‐grade neutropenia and infections were more frequent with palbociclib plus ET (82.1% and 59.2%, respectively) than with ET (5.1% and 39.5%). The hazard ratios were 1.6 ( p = .0995) for grade 3/4 infections, 1.8 ( p = .4358) for grade 3/4 viral infections, 1.4 ( p = .0001) for infections, and 30.8 ( p < .0001) for neutropenia. Febrile neutropenia was reported in 1.4% of patients receiving palbociclib plus ET. Cumulative incidence of all‐grade hematologic adverse events in both arms peaked during the first year of treatment and plateaued over the 5 subsequent years. Interstitial lung disease was reported in 13 patients receiving palbociclib plus ET and 3 receiving ET. Conclusion: This 5‐year, long‐term analysis demonstrated that palbociclib plus ET has a consistent and stable safety profile and is a safe treatment for patients with HR+/HER2− ABC. Implications for Practice: Several treatments for patients with breast cancer are associated with long‐term or latent adverse events. This long‐term, 5‐year analysis demonstrated that palbociclib plus endocrine therapy has a consistent and stable safety profile without cumulative or delayed toxicities. These results further support palbociclib plus endocrine therapy as a safe and manageable treatment in clinical practice for patients with hormone receptor‐positive/human epidermal growth factor receptor 2‐negative advanced breast cancer. Abstract : This updated analysis based on data pooled from the three PALOMA studies is the largest long‐term analysis, to date, of the safety of a CDK4/6 inhibitor in combination with endocrine therapy for the treatment of advanced breast cancer.